Optical detection of paramagnetic centres: from crystals to glass-ceramics - Rogulis, Uldis (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2016)
An unambiguous attribution of the absorption spectra to definite paramagnetic centres identified by the EPR techniques in the most cases is problematic. This problem may be solved by applying of a direct measurement techniques — the EPR detected via the magnetic circular dichroism, or briefly MCD–EPR. The present survey reports on the advantages and disadvantages applying the MCD–EPR techniques to simple and complex paramagnetic centres in crystals as well as glasses and glass-ceramics.